Some Families of Differential Equations Associated with the Hermite-Based Appell Polynomials and Other Classes of Hermite-Based Polynomials - Srivastava, H. M.; Ozarslan, M. A.; Yilmaz, Banu (Univ Nis, Fac Sci Math, 2014)
Recently, Khan et al. [S. Khan, G. Yasmin, R. Khan and N. A. M. Hassan, Hermite-based Appell polynomials: Properties and Applications, J. Math. Anal. Appl. 351 (2009), 756-764] defined the Hermite-based Appell polynomials by G (x, y, z; t) := A(t) . exp(xt + yt(2) + zt(3)) = Sigma(infinity)(n=0) (H)A(n)(x, y, z) t(n)/n! and investigated their many interesting properties and characteristics by using operational techniques combined with the principle of monomiality. Here, in this paper, we find the differential, integro-differential and partial differential equations for the Hermite-based Appell polynomials via the factorization method. Furthermore, we derive the corresponding equations for the Hermite-based Bernoulli polynomials and the Hermite-based Euler polynomials. We also indicate how to deduce the corresponding results for the Hermite-based Genocchi polynomials from those involving the Hermite-based Euler polynomials.
Keywords: Appell and Hermite polynomials; Bernoulli and Euler polynomials; Hermite-based Appell polynomials; Hermite-based Bernoulli polynomials; Hermite-based Euler polynomials; Hermite-based Genocchi polynomials; Partial di ff erential equations; Monomiality principle; Quasi-monomial polynomials